Employment opportunities of refugee women in Germany are improving despite starting at a disadvantage - Adriana R. Cardozo (DIW Weekly Report, 2023)
The majority of refugee women who arrived in Germany during the peak of the refugee crisis between 2013 and 2019 are unemployed. Using data from the IAB-BAMF-SOEP Survey of Refugees, this study investigates the contributing factors for refugee women's limited labor market participation. Results show that a combination of low levels of education compared to the German population, slow progress in language acquisition, and traditional roles in the division of paid and unpaid work within the family are barriers to women's labor market integration. Nevertheless, the share of employed refugee women has doubled. Moreover, the share of women with poor German skills has decreased by half, while the share of women with moderate or good German skills has increased. Additionally, the share of young refugee women participating in an educational program has tripled. These developments show that refugee women have made progress in integrating into the labor market. Therefore, it is urgently recommended to expand existing integration measures that are tailored to women.
Keywords: J15; J22; F22; 330; Refugees; integration; labor force participation; language skills of refugees